How trypanosomes cope with oxidative stress - Flohe, Leopold (Henry Stewart Talks, 2007)
Trypanosomes: causative agents of neglected diseases, Uniqueness of redox metabolism in trypanosomes, Detoxification of hydroperoxides and peroxynitrite, Biosynthesis and function of trypanothione, Validation of targets for trypanocidal drugs
Archived at 2018/05/31